Effect of geometrical parameters on boiling heat transfer and pressure drop in micro finned micro gap - Ahmed, Shugata; Hasan, Muhammad Hasibul; Ismail, Ahmad Faris; Sulaeman, Erwin (2015)
Micro gap heat sinks are potential candidates of evaporative cooling. Additional fins in micro gap enhance heat transfer rate by increasing surface area and generating turbulence. The scope of this paper is to numerically investigate the influence of various geometrical parameters on thermal and hydraulic performance of a micro finned micro gap during flow boiling. For this purpose, flow boiling of water in a micro finned micro gap heat sink has been simulated using FLUENT 14.5 release. Thermal resistance and pressure drop have been calculated for various fin width-to-fin spacing ratio and ratio of base thickness-to-micro gap height. The results demonstrate that thermal resistance decreases for increasing both ratios. However, the descending rate is inconsistent. For higher ratios, decrement rate of thermal resistance is very slow, while pressure drop is very high. Hence, it is suggested that the dimensions should be optimized for extensive cooling performance.